L2 Acquisition of English Binding Domains - Wells, Terri L (MORPHOLOGY AND ITS INTERFACES IN SECOND LANGUAGE KNOWLEDGE, Beck, Maria-Luise [Ed], Amsterdam: John Benjamins, 1998, pp 227-256, 1998)
Second-language (L2) acquisition of English local binding is examined focusing on the roles of anaphor type & verbal morphology. N. Chomsky's (1981) binding theory & L. Progovac's (1992) revised version, the relativized subject analysis, are reviewed, along with L2 studies that employ these approaches. In the present study, three procedures are used to evaluate the binding knowledge of nonnative speakers of English (N = 31 Chinese speakers): truth-value, oral translation, & grammaticality judgment tasks. Native speaker controls (N = 38) contributed comparative data. Overall results indicate direct relationships between the acquisition of overt morphological agreement & binding domain & between representation of anaphor & binding domain. L2 learners who had not yet acquired English morphological agreement or the XP anaphor type accepted long-distance binding, whereas learners who had already acquired morphological agreement allowed long-distance binding in infinitival clauses but required local binding in tensed clauses. Contrary to expectations, learners who had acquired the XP anaphor did not require local binding. In summary, when learners demonstrate acquisition of morphological agreement in English, they usually also show exclusively local binding; however, the reverse situation does not hold. The problems these findings pose for Progovac's analysis are discussed, & T. Reinhart & E. Reuland's (1991) binding framework is shown to better integrate the finding of a polymorphemic anaphor with the finding of the constraining effect of finiteness on long-distance binding. 8 Tables, 3 Appendixes, 34 References. C. Brennan